India-Myanmar relations : historical links to contemporary convergences - Ghosh, Lipi (ed.) (New Delhi, 2016)
In this book,the Indian legendary texts call it Suvarna Bhumi or the Golden Land; its colonial masters called it Burma and its military government renamed it as Myanmar. Whatever the name might be, the country has long been in India?s cultural, historical and political consciousness. Essentially a foreign policy document, this book deals in detail with the geo-strategic importance and relevance of Myanmar to India?s Look East Policy, as narrated by India?s ambassador to Myanmar during 1990?92. It is partly anecdotal and partly historical in nature, providing a first-hand account of Myanmar?s political turbulence and India?s changing policies under three different governments.
Keywords: International Relations